KATA KERJA DALAM BAHASA INGGRIS DAN BAHASA KONJO (SUATU ANALISIS KONTRASTIF) - ALI, NOVITA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTÂ The research which entitled, â€œVerbs in English and Konjo Language: A Contrastive Analysisâ€ aims at classifying, identifying and analyzing the kinds of verbs in these two languages and finding out the similarities and differences between both languages. Â The English data have been collected from English books â€œModern Englishâ€ by Marcella Frank 1972 and the articles on internet, whereas the data of Konjo Language have been collected from informants. Â In English, the kinds of verbs may be classified by complement of verb and form of verb involves predicating or linking verbs, transitive or intransitive verbs, reflexive verbs, auxiliary or lexical verbs and finite or non-finite verbs and in Konjo language it concerns predicating or linking verbs, transitive or intransitive verbs and lexical verbs. Theoretically, this research gives contribution toward the knowledge development in contrastive analysis especially verbs in English and Konjo language. Practically, this research can be used as a reference for further research.Â  Â ---------------------Keywords: Kinds of Verbs in English, Konjo Language, Contrastive Analysis.